Strategic Transformation In Uncertain Situation For UMKM At Desa Banjarsari Kecamatan Cerme Kabupaten Gresik - Edy Sulistiyawan; Siti Isthikoroh; Untung Lasiyono; Moch. Munir Rachman; M. Afrizal Miradji; Noerchoidah; Imam Chambali; Ali Hasan (Fakultas Ekonomi, Universitas PGRI Adi Buana Surabaya, 2022)
The PPM program carried out by a team of lecturers and students at the Adi Buana PGRI Graduate School, Surabaya, has had a positive impact on MSME actors in Banjarsari Village, Cerme District, Gresik Regency in dealing with the current uncertain situation. So that MSME actors can anticipate situations that occur for the existence of MSME businesses. The PPM program began in the post-pandemic period for MSMEs in Banjarsari Village, Cerme District, Gresik Regency to anticipate uncertain business situations, a strategy was needed that was able to enable MSMEs to anticipate uncertain economic conditions. Uncertainties like today (and for who knows how long) make it difficult for many MSMEs, so they need to review and reformulate their strategic plans. The ability of MSMEs to deal with uncertain economic situations and conditions keeps MSMEs running well. The method for implementing the PPM program is carried out in several stages, namely: counseling, mentoring, and evaluation of implementation. Activities that can be carried out to improve the ability to implement the strategy are: 1). Innovation; 2). Collaboration ; 3). Experience; 4). Infrastructure Modernization; 5). Success of Operational Process; 6).Information and Insights.